Work-leisure orientations of nascent professionals and entrepreneurs. - Lee, Samantha Yuan Zhen. (2011)
This study used Holland’s RIASEC typology to identify nascent professionals and entrepreneurs. Using three high-point RIASEC codes, it was established that nascent professionals are high in Investigative(I)-Realistic(R)-Conventional(C) and nascent entrepreneurs are high in Enterprising(E)-Artistic(A)-Realistic(R). To understand the work-leisure relationship, property vector fitting was used to map the leisure interests into a two-dimensional RIASEC circumplex. Distinctive patterns in the perception of work-leisure interests were identified for nascent professionals and entrepreneurs. To nascent professionals, leisure activities occur in opposition to their work activities where overlaps occur only when appropriate. On the other hand, nascent entrepreneurs perceive their leisure interests as an extension to their work activities where overlaps between the two can occur without issues.